Analisis Penggunaan Strategi Pembelajaran dalam Pembelajaran Aqidah Akhlak di SDIT Nurul Ilmi Medan Estate - Adinda, Febby; Darmawan, Fery; Wijaya, Candra (Tarbiatuna: Journal of Islamic Education Studies, 2025)
Aqidah Akhlak learning at the elementary school level plays a strategic role in shaping the Islamic character and personality of students from an early age. The learning strategies used by teachers are crucial in determining the effectiveness of instilling values of faith and morality in students. This study aims to analyze the use of learning strategies in the Aqidah Akhlak subject at SDIT Nurul Ilmi Medan Estate. This research employed a descriptive qualitative approach with data collected through observation, in-depth interviews with two teachers and the principal, as well as documentation of learning activities. The results show that teachers in this school apply a variety of learning strategies, including interactive lectures, storytelling, group discussions, visual media (videos), and contextual case studies. These strategies are tailored to the characteristics and needs of students and are aligned with the learning objectives of Aqidah Akhlak, namely to shape students who are able to internalize and practice Islamic teachings in daily life. However, teachers still face several challenges, such as differences in student characteristics, limited learning resources, and time constraints. Efforts to overcome these obstacles include individualized approaches to students, adaptive teaching methods, and reflective forums and teacher training provided by the school. This study concludes that effective learning strategies in Aqidah Akhlak must be varied, reflective, and capable of addressing the affective aspects of students, so that value-based education can take place meaningfully.